To Investigate the Factor of Self-Efficacy Against the Employability Among University Graduates in Penang, Malaysia with Internship as Intervening Variable - Dr Yeoh Wee Win (Web of Journals Publishing, 2023)
The research study had been conducted with the intention to investigate the factor of self-efficacy against the employability among the university graduates in Penang, Malaysia where the study will include the internship factor as the intervening variable. The self-effacement had been highly refenrece as the major driving factors among the university graduates which potentially will lead to creating positive contribution towards the ability for the individuals to gain better prospects and opportunities to be employed in the competitive market. It is also known that Penang, Malaysia had been identified as the geographical location for the target population which is been a fitting choice where the competitiveness of the employability of the job market had been very high. The study continues in delivering the quantitative study research design by conducting the data collection through the questionnaire distribution towards 150 respondents that had recently joined the employment market in Penang. The result had shown the outcome where the findings had provide the supporting evidence showing no existence of the significant relationship between the self-efficacy among the university graduates affecting the employability in the job market. Besides, the intervening variable of internship had not shown the significant in the intervening role in the regression model suggesting that the internship factor appears to be irrelevance when comes to affecting the employability opportunity in the job market in Penang. The conclusion of the study had opened doors to new research scope and area of interest which can be proceed by the future researchers.
Keywords: Penang, Malaysia, self-efficacy, employment, internship.